Sacrificing Catfish as Marriage Tradition in Indonesia in ‘Urf Perspective - Rabbany, Muhammad Iqbal Mahbub; Sudirman, Sudirman (Universitas Islam Sultan Agung, 2021)
The paper examines the Indonesian community's marriage tradition in Yogyakarta, the-so-called Mbeleh Lele (sacrificing catfish), which has been implemented for several generations. This marriage tradition requires a couple who will marry to slaughter a pair of catfish beforethe ceremony of a marriage contract. This empirical legal research uses the socio-legal approach with the interview as primary data and related books as secondary data. This study applies a descriptive analysis method with the ‘urf (Islamic theory of tradition) as the tool of analysis. Finally, the research shows that the Yogyakarta community's views towards Mbeleh Lele Tradition are divided intotwo types: prominent leader and general people. The prominentleaders firmly believe that there will be a negative effect if the tradition is not implemented. Meanwhile, the general people say that they obey the culture when they experience the adverse effect. In the ‘urf perspective, the Mbeleh Lele tradition can be categorized as the ‘urf sahih (correct tradition) because it meets the required condition.